Peningkatan Keterampilan Petani pada Usaha Budidaya Ikan Lele dengan Teknologi Kawin Suntik - Norman Prayogo; Purnama Sukardi; Asrul Sahri Siregar (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Answering higher challenge of occupational area along with smaller available job opportunities, it is needed business creation for the society based on local resources and science and technology. One of aquaculture activity that conducted was application of injected spawning technique among and rearing larvae of catfish. The objective of this activity, skill, and increase income also as a new economic activity for students in Farmer Group Mandiri Jaya, Sokaraja, Banyumas. Research method comprised of activities like transfer of knowledge, training, demonstration plot and application of production for 4 months. Evaluation of technology transfer activity viewed from questionnaire value, training and demonstration plot viewed from ability and of participant to produce seed and profit gained. Generally, knowledge and skill of participant was improved. However viewed from production yield was still varied Evaluasi kegiatan transfer teknologi dilihat dari nilai kuisioner , pelatihan dan percontohan dilihat dari kemampuan dan keterampilan penguasaan teknologi sedangkan aplikasi produksi adalah kemampuan peserta menghasilkan benih dan keuntungan yang diperoleh. Secara umum pengetahuan, keterampilan peserta meningkat. Namun ditinjau dari segi hasil produksi masih bervariasi.